Performance of requirements of a supply with information of management by pulse protection against explosion and fire at the chemical enterprise - Кряжич, Ольга Олександрівна (Ukrainian Information Security Research Journal, 2012)
In article of research concerning support of observance of conditions of timeliness, consistency and completeness of the information are resulted. It is necessary for management of pulse protection against explosion and a fire at the chemical enterprise. Features of the offered technological decision are specified. Also processes of monitoring of the information and support of information safety are defined. Commands of management and identification of streams of the information in a package of software products are specified.